Prognostic implications of CD9 in childhood acute lymphoblastic leukemia: insights from a nationwide multicenter study in China - Leung, Kam Tong; Cai, Jiaoyang; Liu, Yu; Chan, Kathy Yuen Yee; Shao, Jingbo; Yang, Hui; Hu, Qun; Xue, Yao; Wu, Xuedong; Guo, Xia; Zhai, Xiaowen; Wang, Ningling; et al. (Leukemia, 2024)
The outcomes of children with acute lymphoblastic leukemia (ALL) have been incrementally improved with risk-directed chemotherapy but therapy responses remain heterogeneous. Parameters with added prognostic values are warranted to refine the current risk stratification system and inform appropriate therapies. CD9, implicated by our prior single-center study, holds promise as one such parameter. To determine its precise prognostic significance, we analyzed a nationwide, multicenter, uniformly treated cohort of childhood ALL cases, where CD9 status was defined by flow cytometry on diagnostic samples of 3781 subjects. CD9 was expressed in 88.5% of B-ALL and 27.9% of T-ALL cases. It conferred a lower 5-year EFS and a higher CIR in B-ALL but not in T-ALL patients. The prognostic impact of CD9 was most pronounced in the intermediate/high-risk arms and those with minimal residual diseases, particularly at day 19 of remission induction. The adverse impact of CD9 was confined to specific cytogenetics, notably BCR::ABL1 + rather than KMT2A -rearranged leukemia. Multivariate analyses confirmed CD9 as an independent predictor of both events and relapse. The measurement of CD9 offers insights into patients necessitating intervention, warranting its seamless integration into the diagnostic marker panel to inform risk level and timely introduction of therapeutic intervention for childhood ALL.